POLITIK ISLAM DI INDONESIAANTARA SAKRALISASI DAN SEKULARISASI - Tri Subhi Abdillah (Sekolah Tinggi Agama Islam Indonesia Jakarta, 2018)
The struggle of Muslim politicians in Indonesia is at an alarming point. Thisis evidenced by the vote acquisition of Islamic parties in the 2009 electionswhich dropped quite sharply. In addition, Islamic aspirations are not heard.There were no loud demands for sharia enforcement or making Islam thebasis of the state. This study shows how the failure of Muslims in theIndonesian political scene and the success of of secularists